Determinant Factors of the Quality of Life in Children with Osteogenesis Imperfecta during the COVID-19 Pandemic - Rochmah, Nur; Mustikasari, Rahma Ira; Faizi, Muhammad; Irwanto, Irwanto (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Osteogenesis imperfecta (OI) is a common chronic illness with increasing prevalence. Coronavirus disease 2019 (COVID-19) and large society restriction policies in Indonesia cause problems and might affect the quality of life (QoL) of children with OI. Objective: To evaluate determinant factors that affect OI children's QoL pre and during the first year of the COVID-19 pandemic. Method: This was a cross-sectional study design conducted in the Pediatric Endocrinology Outpatient Clinic, Dr. Soetomo Hospital, Surabaya, Indonesia, during the COVID-19 pandemic in 2020 to assess the patient’s QoL. This study used a diagnostic group with questionnaires. The instrument included the Pediatric Quality of Life Inventory 4.0 Generic Score, a standardized interview questionnaire comprising questions on the participant characteristics and determinant factors pre and during the COVID-19 pandemic. Analysis of determinant factors pre and during the pandemic used McNemar. Correlation between determinant factors and QoL used linear regression for physical and emotional dimensions and logistic regression for social, school, and total score. Result: Of the 22 children with OI, 19 had fear of visiting the hospital (p < 0.001), and 16 had obstacles to visiting the hospital (p < 0.01). The determinant factors for taking calcium and/or vitamin D supplementation pre and during the COVID-19 pandemic affected school functioning (p = 0.015) and the total score (p = 0.027). Conclusion: The significant risk factors pre and during COVID-19 were fear of and obstacles to visiting the hospital. Supplementation of calcium and/or vitamin D pre and during the COVID-19 pandemic significantly impacted school functioning and the total score.